2014
DOI: 10.1021/am502382n
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Mixed-Charge Copolymers As Wound Dressing Biomaterials

Abstract: Herein, a pseudozwitterionic structure bearing moieties with mixed positive and negative charges is introduced to develop a potential biomaterial for wound dressing applications. New mixed-charge matrices were prepared by copolymerization of the negatively charged 3-sulfopropyl methacrylate (SA) and positively charged [2-(methacryloyloxy)ethyl] trimethylammonium (TMA) onto expanded polytetrafluoroethylene (ePTFE) membranes. The charge balance was effectively regulated through the control of the initial SA/TMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 47 publications
0
42
0
Order By: Relevance
“…The results (Table ) showed that all of the ξ potentials were close to zero; this suggested that almost no net electric charge was carried in the PSTG copolymers. This may have been due to the similar chemical reactivities of the TMA monomers and SA monomers in aqueous solution, as confirmed previously . Therefore, the charge‐bias variation of the PSTG copolymers could be controlled at a low level via the regulation of the feed ratio of the SA to TMA monomer at 1:1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results (Table ) showed that all of the ξ potentials were close to zero; this suggested that almost no net electric charge was carried in the PSTG copolymers. This may have been due to the similar chemical reactivities of the TMA monomers and SA monomers in aqueous solution, as confirmed previously . Therefore, the charge‐bias variation of the PSTG copolymers could be controlled at a low level via the regulation of the feed ratio of the SA to TMA monomer at 1:1.…”
Section: Resultsmentioning
confidence: 99%
“…reported a systematic study of the effect of charge‐bias variations in poly(3‐sulfopropyl methacrylate‐ co ‐methacrylatoethyl trimethyl ammonium chloride) copolymers on the hemocompatibility in human blood plasma and concluded that pseudo‐zwitterionic copolymers of poly(3‐sulfopropyl methacrylate‐ co ‐methacrylatoethyl trimethyl ammonium chloride) with an overall charge neutrality had the best antifouling, anticoagulant, and antihemolytic activities. Jhong et al . further developed a wound dressing by growing pseudo‐zwitterionic brushes onto polytetrafluoroethylene membranes and investigated the role of the membrane surface charge on the essential wound dressing properties for wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudo-zwitterionic materials (or mixed charged polymers), as newer classes of biomedical surface modifiers, are enhanced semi-ZW structures with positively dual charged structures that are not affected by other chemical functional groups due to higher stability. Accordingly, they have been introduced as better candidates for improving hemodialysis membranes by surface immobilization or forming hydrogels [68][69][70]. Table 1 offers some of the most recent efforts focused on zwitterionization of membrane surfaces.…”
Section: Hemocompatibility Enhancementsmentioning
confidence: 99%
“…Whole blood was either fractionated by centrifugation to obtain red blood cells concentrate, white blood cell concentrates or platelet-rich plasma, or used as is in blood adhesion tests. The method for blood fractionation as performed in this study is published elsewhere [39]. 0.8 mL Of concentrate of interest or of whole blood was incubated at 37°C for 2 h with membrane samples (diameter: 1 cm) positioned in a well-plate placed in an incubator.…”
Section: Antifouling and Hemocompatible Properties Of Pp Membranesmentioning
confidence: 99%